STRATEGI PENGEMBANGAN USAHATANI CABAI RAWIT DI KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Fahmid Yusuf; Asda Rauf; Amir Halid (Agrinesia: Jurnal Ilmiah Agribisnis, 2018)
The purpose of this research is: (1) knowing about the cayenne pepper performance in Dungaliyo District,(2) analyze the factors that influence the development of cayenne pepper agribusiness and (3) develop strategy of agribusiness development of chili pepper in District Dungaliyo Gorontalo District. This research was conducted in September - October 2017 in District Dungaliyo Gorontalo District. The method used in this research is to use survey method with data analysis using descriptive analysis technique and SWOT analysis. The results of this study show that: (1) the performance of chili pepper farming in Kecamatan Dungaliyo Gorontalo Regency has applied appropriate farming techniques because the farmers have experience in farming and often follow the training directly from extension workers who provide training on cultivation of cayenne pepper; (2) factors influencing chili development strategy include strength factor that is experience of farmer in cayenne pepper, weakness factor of product that easily damaged, while opportunity factor include support from local government, and threat factor is pest / disease; (3) the strategy of developing Rawit Chili in Dungaliyo sub-district, Gorontalo regency is located in quadrant I that support aggressive strategy or SO (strenght - opportunity) by using the strength and opportunity to minimize the existing weaknesses and threats so as to make progress.